Exercise Mode in Heart Failure: A Systematic Review and Meta-Analysis - Jamie Edwards; Nesan Shanmugam; Robin Ray; Fadi Jouhra; Jennifer Mancio; Jonathan Wiles; Anna Marciniak; Rajan Sharma; Jamie O’Driscoll (Sports Medicine - Open, 2023)
Abstract Background Optimising exercise prescription in heart failure (HF) with a preserved (HFpEF) or reduced (HFrEF) ejection fraction is clinically important. As such, the aim of this meta-analysis was to compare traditional moderate intensity training (MIT) against combined aerobic and resistance training (CT) and high-intensity interval training (HIIT) for improving aerobic capacity (VO2), as well as other clinically relevant parameters. Methods A comprehensive systematic search was performed to identify randomised controlled trials published between 1990 and May 2021. Research trials reporting the effects of MIT against CT or HIIT on peak VO2 in HFpEF or HFrEF were considered. Left-ventricular ejection fraction (LVEF) and various markers of diastolic function were also analysed. Results Seventeen studies were included in the final analysis, 4 of which compared MIT against CT and 13 compared MIT against HIIT. There were no significant differences between MIT and CT for peak VO2 (weighted mean difference [WMD]: 0.521 ml min−1 kg−1, [95% CI] =  − 0.7 to 1.8, P fixed = 0.412) or LVEF (WMD: − 1.129%, [95% CI] =  − 3.8 to 1.5, P fixed = 0.408). However, HIIT was significantly more effective than MIT at improving peak VO2 (WMD: 1.62 ml min−1 kg−1, [95% CI] = 0.6–2.6, P random = 0.002) and LVEF (WMD: 3.24%, [95% CI] = 1.7–4.8, P random < 0.001) in HF patients. When dichotomized by HF phenotype, HIIT remained significantly more effective than MIT in all analyses except for peak VO2 in HFpEF. Conclusions HIIT is significantly more effective than MIT for improving peak VO2 and LVEF in HF patients. With the exception of peak VO2 in HFpEF, these findings remain consistent in both phenotypes. Separately, there is no difference in peak VO2 and LVEF change following MIT or CT, suggesting that the addition of resistance exercise does not inhibit aerobic adaptations in HF. Graphical Abstract